Influence of an Orthoptic Exercises on Near Point of Convergence (Medical Forum Monthly, 2021)
Objective: To evaluate the influence of Orthoptic exercise on near point of converge in patients with Convergence insufficiency (CI).Study Design: Interventional longitudinal studyPlace and Duration of Study: This study was conducted at the Eye Clinic of Al-Ibrahim Eye hospital Karachi for a period of 8 months October 2020 to April 2021.Materials and Methods: 60 patients with confirmed diagnoses of CI were chosen for the study. All of the patients were prescribed pencil push-up tests as a form of Orthoptic Exercise to reduce CI. The pre and post Near Point of Convergence was determined and compared using the chi-square test with P-value ≤0.05 considered being statistically significant.Results: Significant difference (P-value ≤0.001) was seen in Pre and Post Near Point of Convergence in the group without glasses and the group with glasses.Conclusion: Orthoptic Exercises proved to be influential in improving the Near point of Convergence